PERAN BADAN PERMUSYAWARATAN DESA DALAM PEMBANGUNAN DESA (Studi Kasus di Desa Tetehosi I Kecamatan Gunungsitoli Idanoi Kota Gunungsitoli Provinsi Sumatera Utara)1 - Ardiyansyah Tanjung (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2011)
This study aims at knowing the role of village consultative body in village development in Tetehosi I Village, Gunungsitoli Idanoi Sub district, Gunungsitoli Municipality. This study applies descriptive research method with qualitative approach. The aspects analyzed in this study are the roles of BPD comprising three aspects namely: policy making, supervision, and empowerment. The data collection technique is conducted through indepth interview, participant-observation, and documentation study. The study result shows that the role BPD has not been optimal yet in village development in Tetehosi I Village. The village regulation has not been created yet by BPD member since built in 2007. In conducting of supervision towards the implementation of village development, the BPD member Tetehosi I village does not have a clear mechanism yet. Women empowerment in the membership of BPD Tetehosi I also have not run well, because the 11 members of BPD are men.